2016
DOI: 10.1007/s40145-015-0170-0
|View full text |Cite
|
Sign up to set email alerts
|

Sintering and mechanical properties of β‐SiC powder obtained from waste tires

Abstract: Plasma synthesized SiC powder obtained from quartz and carbonaceous residue of waste tires was successfully sintered at 1925 ℃ by pressureless liquid-phase method using yttria and alumina as sintering aids (T-SiC). Comparison with sintered SiC obtained from commercial powder (C-SiC) put in evidence of similar sintered density (98%T.D.), but much finer microstructure of T-SiC than that of C-SiC. T-SiC also showed higher flexural strength than C-SiC both at room temperature (508 vs. 458 MPa) and at 1500 ℃ (280 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In recent years, with increased demand on natural gas, and the aspiration to strengthen national energy security and increase energy efficiency, the production of synthetic natural gas (SNG) from coal or biomass has aroused widespread concern [9][10][11][12][13]. Being a good potential material, SiC has extensive applications in many fields, especially working in harsh environments as a support due to its excellent properties including high heat conductivity, thermal stability, mechanical strength, and chemical inertness [14][15][16][17][18][19]. SiC has been applied to various reactions, including methane reforming and combustion, Fischer-Tropsch synthesis, isomerization and dehydrogenation, among others [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with increased demand on natural gas, and the aspiration to strengthen national energy security and increase energy efficiency, the production of synthetic natural gas (SNG) from coal or biomass has aroused widespread concern [9][10][11][12][13]. Being a good potential material, SiC has extensive applications in many fields, especially working in harsh environments as a support due to its excellent properties including high heat conductivity, thermal stability, mechanical strength, and chemical inertness [14][15][16][17][18][19]. SiC has been applied to various reactions, including methane reforming and combustion, Fischer-Tropsch synthesis, isomerization and dehydrogenation, among others [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Weibull statistics [1] has been widely employed to model the variability in the fracture strength of brittle ceramics [2][3][4][5][6][7][8]. In general, a two-parameter form of the Weibull function is adopted to give the cumulative failure probability, P, of a component or specimen at a given applied stress, , as [2]:…”
Section: Introductionmentioning
confidence: 99%
“…This was caused by the growth of the SiC grains. According to the calculated phase diagram, an eutectic liquid phase is formed in the Y 2 O 3 -Al 2 O 3 -SiO 2 system at the temperatures between 1635 and 1644 ℃ by Reactions (12) and (13) [27]. Furthermore, Liang et al [37] reported that a liquid phase was clearly observed in the pressureless sintered SiC with Al 2 O 3 and Y 2 O 3 additives at the temperature of 1680 ℃.…”
Section: Microstructure Of Sic/al 4 Sic 4 Composites and Al 4 Sicmentioning
confidence: 99%
“…Al 4 SiC 4 has good combination of properties, such as low density (3.03 g/cm 3 ), high melting point (2080 ℃), high compressive strength conductivity into the Al 4 SiC 4 matrix. Silicon carbide (SiC) is a promising candidate, because of its high hardness, excellent mechanical properties at high temperatures, and high thermal conductivity [12][13][14][15]. The SiC particles have successfully been used to reinforce titanium silicon carbide (Ti 3 SiC 2 ) matrices [16][17][18].…”
Section: Introduction mentioning
confidence: 99%